2021
DOI: 10.1109/access.2021.3089210
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment Methods to Evaluate the Performance of Edge Detection Algorithms for Digital Image: A Systematic Literature Review

Abstract: A segmentation process is usually required in order to analyze an image. One of the available segmentation approaches is by detecting the edges on the image. Up to now, there are many edge detection algorithms that researchers have proposed. Thus, the purpose of this systematic literature review is to investigate the available quality assessment methods that researchers have utilized to evaluate the performance of the edge detection algorithms. Due to the vast number of available literature in this area, we li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…The specific method is to first expand the height and width of the depth image to 1.437 times of the original image respectively, and then select the pixels with row coordinates of 25 and column coordinates of 18 in the image as the upper left corner of the clipping area, and the interception resolution is 700 × 540, and then the intercepted area is enlarged to a resolution of 1400 by bilinear interpolation × 1 080 depth image, and finally 1 024 is intercepted in the central area × 1 024 pixel depth image. At this time, the depth image and color image can realize pixel mapping, and these processed depth images can be used to generate depth mask annotation samples, and in the number of samples and samples [16]. The content is consistent with the sample set of RGB image.…”
Section: Construction Of Materials Methods Data Set a Test Materials ...mentioning
confidence: 98%
“…The specific method is to first expand the height and width of the depth image to 1.437 times of the original image respectively, and then select the pixels with row coordinates of 25 and column coordinates of 18 in the image as the upper left corner of the clipping area, and the interception resolution is 700 × 540, and then the intercepted area is enlarged to a resolution of 1400 by bilinear interpolation × 1 080 depth image, and finally 1 024 is intercepted in the central area × 1 024 pixel depth image. At this time, the depth image and color image can realize pixel mapping, and these processed depth images can be used to generate depth mask annotation samples, and in the number of samples and samples [16]. The content is consistent with the sample set of RGB image.…”
Section: Construction Of Materials Methods Data Set a Test Materials ...mentioning
confidence: 98%
“…The systematic literature review was conducted by referring to the guidelines found in [7]. The findings have been published on the IEEE, Wiley, MDPI, Hindawi, and Scopus websites.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Edge detection contributes a lot of important information. The edge detection algorithm represents an image with a contour that makes it a recognizable object with detected edges [8][9]. One of the most important features of the edge detection method is that precise edge detection accompanies good object orientation in the image [10].…”
Section: Canny Edge Detectionmentioning
confidence: 99%